Rare presentation and resection of giant cell tumor invading the middle ear and skull base: A case report - Joshua M. Cohen; Geena Jung; Hailey Reisert; Yi-Hsueh Lu; Genesis Liriano; Bradley A. Schiff; Evan S. Garfein; Andrew J. Kobets (JPRAS Open)
Giant cell tumors (GCTs) are common benign bone tumors found in young adults, frequently occurring in the long bones but rarely in the skull. Although considered benign, GCTs have the potential to be aggressive, destroying surrounding tissue. Here, we present the unusual case of a patient with a GCT of the middle ear and skull base. A 19-year-old male with an extensive giant cell tumor underwent surgical resection by a multidisciplinary team consisting of otolaryngology, neurosurgery, and plastic and reconstructive surgery. The mass was grossly resected, and a cervicofacial flap allowed for reconstruction with optimal cosmesis, a procedure not described for GCTs. This approach allowed for excellent wound healing without tumor recurrence. Gross total resection remains the most effective treatment for GCTs, minimizing radiation exposure and recurrence risk. However, an optimal surgical approach for skull GCTs has yet to be described. Skull-base GCTs present a challenge due to their complex anatomy and neurovascular elements. Further, the high rates of local recurrence make gross resection the goal of treatment, though this is difficult to achieve. The present case was successfully managed by extensive multidisciplinary surgical resection, highlighting the necessity of collaborative effects to achieve gross total resection and positive aesthetic outcomes.